Elevated prolactin levels before endometrial transformation negatively impact reproductive outcomes in frozen embryo transfer cycles under hormone replacement therapy - Yaxin Wang; Fei Sheng; Li Cao; Jiaying Ni; Meishan Wang; Yan Yang; Jiating Wang; Jingyi Lu; Jian Zhou; Hongfang Shao (BMC Pregnancy and Childbirth)
Abstract Introduction Prolactin (PRL) plays a key role in the regulation of reproductive functions. However, its impact on outcomes in infertility women undergoing assisted reproductive technology remains unclear. This study aimed to examine the relationship between PRL levels and reproductive outcomes in frozen embryo transfer (FET) cycles under hormone replacement therapy (HRT). Materials and methods A total of 1212 FET cycles under HRT were included from a single center in Shanghai between March 2013 and June 2023. PRL levels were measured on the day before progesterone-induced endometrial transformation and participants were stratified according to the near-quartiles cut-points of PRL. Logistic regression analyses were performed to assess the associations between different PRL levels and reproductive outcomes. Results Live birth rate was significantly lower in the highest PRL group (> 20ng/ml) compared with the rest of the groups. In line with this, the multivariable adjusted ORs with ascending PRL categories (≤ 10.0 ng/ml, 10.1–15.0 ng/ml, 15.1–20.0 ng/ml, and > 20.0 ng/ml) for live birth rates were 1.07 (95%CI: 0.75–1.52), 1.00, 0.89 (95%CI: 0.63–1.24) and 0.53 (95%CI: 0.37–0.75), respectively. Furthermore, elevated PRL levels were also significantly associated with a reduced chance of clinical pregnancy and an increased risk of early miscarriage. Conclusions High PRL levels before endometrial transformation are significantly associated with poor reproductive outcomes. These findings highlight the importance of measuring PRL during endometrial preparation in HRT-FET cycles, although PRL monitoring is not usually performed during this period in current clinical routine.